Склоемалеві покриття для крупногабаритних сталевих виробів - Голеус, Віктор Іванович; Кислична, Раїса Іванівна; Нагорна, Тетяна Іванівна; Науменко, Світлана Юріївна (НТУ "ХПІ", 2016)
Розроблені одношарові емалеві покриття, що характеризуються високими міцністю зчеплення і блиском, гарною оплавленістю, добрими експлуатаційними та декоративними характеристиками і можуть використовуватись для емалювання крупногабаритних виробів господарчо-побутового і технічного призначення. Встановлено раціональне кількісне співвідношення досліджуваних фрит у складі емалевих покриттів та визначено позитивний вплив наповнювачів на основні характеристики склошару. Досліджено реологічні властивості шлікерів і виявлено їх вплив на якість склопокриттів.

Developed single-layer enamel coating, characterized by a high adhesive strength and gloss, good sealing, operational and decorative properties and can be used for enamelling of large-sized products for household and industrial uses. Established a rational quantitative relationship experienced as part of the enamel frit coverages and defined a positive impact on the basic characteristics of fillers glass-layer. The rheological properties of the slurries and found their impact on the quality of the glass coatings. We get quality one-layer coating of dark brown color, which have high density, gloss and other performance properties, as evidenced by production tests in the conditions of enamelling plants in the cities of Kerch and Novomoskovsk.
Glass-coatings for large steel products
Keywords: склоемаль; фрита; покриття одношарові; властивості; консистенція шлікеру; міцність зчеплення; вироби крупногабаритні; enamels; frits; single-layer coatings; large-sized products